Examining the Representation of Women as Wise Authorities and Alpha Women in the Book of Proverb - Bimbing Kalvari; Idrus Sasirais (Sekolah Tinggi Teologi Intheos Surakarta, 2023)
The Book of Proverbs contains numerous moral teachings and wise sayings. However, the representation of women in this book is often depicted as unequal and unjust, particularly regarding their status and roles. This article aimed to assess the representation of women in the Book of Proverbs and explore how they can be perceived as authoritative sources of wisdom and as alpha women. Through an exegetical study that examines theologians’ views on women’s representation in the Book of Proverbs, the role of women in this book will be analyzed to reclaim their status as wise individuals and strong women in both private and public realms. This understanding is crucial for creating a gender-balanced and equitable interpretation that is not influenced by patriarchal cultural norms.